Impact of VR on Learning Experience compared to a Paper based Approach - Kolarik, Stella; Schlüter, Christoph; Ziolkowski, Katharina (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2024)
Different learning theories encourage different kinds of learning approaches. Following constructivist theories, learning experiences should be realistic in order to facilitate learning. Virtual Reality (VR) serious games could be a realistic learning approach without the challenges of the real situation. The serious game InGo allows a user to learn the intralogistics process of receiving goods. In this work we explore whether learning in VR is more effective concerning learning success and learning experience than traditional learning approaches. No significant difference between the two approaches concerning learning success is found. However, other factors that have a long term effect on learning, such as intrinsic motivation, flow and mood, are significantly higher for the VR approach. Thus, our research fits with past research which indicated the high potential of VR based learnig and educational games. This work encourages future research to compare VR based and traditional learning approaches in the long term.